PEMANFAATAN TEKNOLOGI DIGITAL DALAM PENYUSUNAN PEMBELAJARAN DAN IMPLEMENTASI PERANGKAT PEMBELAJARAN PAI DI MAS BABUSSALAM, ACEH SINGKIL (Institut Ummul Quro Al-Islami Bogor, 2025)
The use of digital technology in education has become an urgent necessity in the modern era. This study aims to analyse the use of digital technology in the development and implementation of Islamic Religious Education (IRE) learning tools at Babussalam Private Madrasah Aliyah (MAS) in Aceh Singkil. The research method used was descriptive qualitative with observation, interview, and documentation study techniques. The results showed that digital technology has made a significant contribution to the planning, implementation, and evaluation of PAI learning. IR teachers are able to utilise digital tools such as word processing applications, presentations, e-learning, and interactive media to develop lesson plans and present material in a more interesting and understandable way for students. However, there are still challenges in the form of infrastructure limitations, teachers' digital literacy, and consistency in the use of technology in learning. This article is expected to contribute to the development of a more effective and sustainable digital-based PAI learning model.